Rethinking feedback in a connected age - Lopes, Ana Paula (2018)
Feedback has long been identified as a core component in the learning process and remains a regular subject of academic research. It can be performed in several forms, for different purposes but the literature emphasizes the undeniable power of feedback on the achievement and development of learning outcomes. This article presents a reflexion about current trends on feedback in higher education and seeks to contribute to deepening the theme and the diverse issues related, in a comprehensive and integrative perspective of the various aspects involved. Different approaches to the concept of feedback, the characteristics of effective feedback, strategies of successful feedback examples and best practices will be considered. We will address recent issues in the literature on the power and challenges of providing feedback in a connected age through technology. There are few instruments that assess the frequency, type and impact of feedback in classrooms, however the enormous quantity of data produced surrounding the interactions in Virtual Learning Environments provides a valuable material to the Learning Analytics field that can be used to improve feedback practices. This research seeks to enhance the learning process over the analysis of dataset to provide informative feedback to learners and educators. In addition, based on a reflexive approach supported by our professional experience performed in the Moodle platform we present some results of how feedback can be used to optimize mathematical understanding. We will also present a brief analysis of the data collected in a survey that seeks to increase the knowledge about students' perceptions regarding this issue.